Binary 2in1 Vectors Improve in Planta (Co)localization and Dynamic Protein Interaction Studies. Issue 3 (13th May 2015) - Hecker, Andreas; Wallmeroth, Niklas; Peter, Sébastien; Blatt, Michael R.; Harter, Klaus; Grefen, Christopher
Abstract : The combination of new generation fluorescent proteins with the 2in1-cloning technique improves (co)localization and protein interaction analyses in vivo. Abstract: Fluorescence-based protein-protein interaction techniques are vital tools for understanding in vivo cellular functions on a mechanistic level. However, only under the condition of highly efficient (co)transformation and accumulation can techniques such as Förster resonance energy transfer (FRET ) realize their potential for providing highly accurate and quantitative interaction data. FRET as a fluorescence-based method unifies several advantages, such as measuring in an in vivo environment, real-time context, and the ability to include transient interactions as well as detecting the mere proximity of proteins. Here, we introduce a novel vector set that incorporates the benefit of the recombination-based 2in1 cloning system with the latest state-of-the-art fluorescent proteins for optimal coaccumulation and FRET output studies. We demonstrate its utility across a range of methods. Merging the 2in1 cloning system with new-generation FRET fluorophore pairs allows for enhanced detection, speeds up the preparation of clones, and enables colocalization studies and the identification of meaningful protein-protein interactions in vivo.